A Compulsory Dispute Resolution Capstone Subject: An Important Inclusion in a 21st Century Australian Law Curriculum - Rachael M Field; Alpana Roy (Legal Education Review, 2017)
The Australian legal profession, and Australian legal education, have experienced significant change over the last three decades. There has, for example, been an exponential increase in the use of forms of dispute resolution (DR) other than litigation to resolve legal disputes, and legal education has evolved to include a stronger focus on the teaching of legal skills and values. This article contributes to the literature arguing that DR should no longer simply constitute part of the elective choices available to law students, but rather should be embedded within the LLB and JD core curricula. First, the article considers the recent scholarship on DR in Australian legal education, most of which supports the view that due to the demands of contemporary legal practice, every graduating law student should now have an opportunity to engage with DR knowledge, skills and attitudes as part of their legal education. Second, the best way to teach DR in the core curriculum is considered. We propose that a capstone DR subject has great potential to support student transition out of law school, to provide closure on their learning, and to promote engagement for deep learning outcomes in the final year.